TINJAUAN HUKUM OPSI MEMBERIKAN DAN/ ATAU MENYEBARLUASKAN DATA PRIBADI NASABAH DALAM PEMBUKAAN REKENING BSI - Septina (Esensi Hukum, 2022)
In order to improve its services, Bank Syariah Indonesia (BSI) provides online bank account opening services, furthermore in the opening bank account form there is an option wether the customers will give and/ or distribute their personal data. This article discusses the validity of the agreement, the protection of customer’s personal data has been given and/or distributed to third parties for commercial purposes and the legal risks may arise. The conclusions of this normative legal research are: first, the clause must comply the objective legal requirements of agreement, including: adequate consideration and legality and subjective legal requirements of agreement, including: mutual assent and capacity such as the age of the customers is at least 17 years old, has a Resident Identity Card and is not in custody; secondly, the protection of customer’s personal data has been given by providing as an option wether the customer will give and/ or distribute their personal data or not; third, the customer cannot reduce the legal risk of leakage of customer’s personal data which can cause the occurrence of crimes